Correlation of Hsp70 Serum Levels with Gross Tumor Volume and Composition of Lymphocyte Subpopulations in Patients with Squamous Cell and Adeno Non-Small Cell Lung Cancer - Gunther, Sophie; Ostheimer, Christian; Stangl, Stefan; Specht, Hanno M.; Mozes, Petra; Jesinghaus, Moritz; Vordermark, Dirk; Combs, Stephanie E.; Peltz, Friedhelm; Jung, Max P.; Multhoff, Gabriele (Frontiers in Immunology, 2015)
Heat shock protein 70 (Hsp70) is frequently found on the plasma membrane of a large number of malignant tumors including non-small cell lung cancer (NSCLC) and gets released into the blood circulation in lipid vesicles. On the one hand a membrane (m)Hsp70-positive phenotype correlates with a high aggressiveness of the tumor, on the other hand, mHsp70 serves as a target for natural killer (NK) cells that had been pre-stimulated with Hsp70-peptide TKD plus low dose interleukin-2 (TKD/IL-2). Following activation, NK cells show an up-regulated expression of activatory C-type lectin receptors, such as CD94/NKG2C, NKG2D and natural cytotoxicity receptors (NCRs; NKp44, NKp46, NKp30) and thereby gain the capacity to kill mHsp70-positive tumor cells. With respect to these results, the efficacy of ex vivo TKD/IL-2 stimulated, autologous NK cells is currently tested in a proof-of-concept phase II clinical trial in patients with squamous cell NSCLC after RCT at the TUM. Inclusion criteria are histological proven, non-resectable NSCLC in stage IIIA/IIIB, clinical responses to RCT and a mHsp70-positive tumor phenotype. The mHsp70 status is determined in the serum of patients using the lipHsp70 ELISA test which enables the quantification of liposomal and free Hsp70. Squamous cell and adeno NSCLC patients had significantly higher serum Hsp70 levels than healthy controls. A significant correlation of serum Hsp70 levels with the gross tumor volume (GTV) was shown for adeno and squamous cell NSCLC. However, significantly elevated ratios of activated CD69+/CD94+ NK cells that are associated with low serum Hsp70 levels were observed only in patients with squamous cell lung cancer. These data might provide a first hint that the innate immune system might get activated by soluble Hsp70 in squamous cell but not adeno NSCLC.